Hypercholesterolemia and 3-Hydroxy 3-Methylglutaryl Coenzyme A Reductase Regulation during Ageing - Laura Trapani; Valentina Pallottini (The Scientific World Journal)
We present here a brief description of the path that cholesterol covers from its intestinal absorption to its effect exerted on some enzyme regulation. Some mechanisms underlying hypercholesterolemia onset and, in particular, the role and the regulation of 3-hydroxy 3-methylglutaryl Coenzyme A reductase (HMGR) during adult life and during aging, have been described. In addition some pharmacological interventions to control proper HMGR regulation and, in turn, cholesterol homeostasis maintenance will be introduced.